Aplikasi Pengelolaan Rumah Berkas Wajib Pajak di Kantor Pelayanan Pajak Pratama - Fitri Nuraeni; Puspa Rahayu (STMIK PONTIANAK, 2016)
AbstractFile management debt collection letter of the taxpayer in the Tax Office Primary use the term home taxpayer files. Where in the maintenance of the file is still using the process of recording data on the ledger and the physical storage of records in a file cabinet. The amount of storage shelves and files are kept very much lead in the file search process takes a long time. Supervision existence archive documents is very difficult to do if you have to check the house when the order to each file.By utilizing databases and application managers, can be designed application manager of the file that works to help the storage of data files and check the existence of a letter to the home archive file. This application design using the Waterfall method using a structured approach flowmap, context diagrams, data flow diagrams and entity relationship diagrams as design data base.Management of application design house taxpayer files, intended in order to overcome the problems that occur in the Collection Section Tax Office Primary, so that the process of debt collection file management taxpayer for faster and easier.Keywords—Home Files, File Collection, Tax Debt, The Taxpayer